FACTORS AFFECTING THE ACCOUNTABILITY OF VILLAGE FUND MANAGEMENT IN BANYUASIN DISTRICT, SOUTH SUMATRA - Ameliana, Voni Adita; Irianto, Bambang Setyobudi; Suparlinah, Irianing (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2023)
This study employs a survey method on village funds in South Sumatra's Banyuasin Regency and aims to determine the influence of competence, organizational commitment, internal control system, and the use of information technology on accountability. The collected data consists of 97 village respondents' apparatus in the Banyuasin region. The findings show that: (1) Competence has no effect on accountability; (2) organizational commitment has no effect on accountability; (3) internal control system has no effect on accountability; and (4) the use of information technology has a positive effect on accountability. In addition to other factors that have been analysed, the implication of the research is an effort to increase accountability in the management of village funds through the use of appropriate information technology. The village government can implement a village government work system based on the use of information technology, such as the village web, which is a tool for disseminating information on village-related activities and supporting information accessibility so that it can reach all circles more effectively, thereby promoting accountability.